• Discover

1. Home >
2. All Categories >
3. Science & Mathematics >
4. Mathematics >
5. Resolved Question
Member since:
June 04, 2010
Total points:
83 (Level 1)

Resolved Question

Show me another »

How do you get this answer by elimination for differential equations?

I have:

3(D+1)x + 3(D-1)y = 6
3(D+1)x + (D+1)(D+2)y = -(D+1)

When I subtract the first equation from the second one, I get:
(D^2 +5)y = -D-7

(D^2 +5)y = -7

How do you get rid of the -D on the right side of the equation? Or am I messing something up in the subtraction?
Member since:
February 03, 2009
Total points:
28,355 (Level 7)

- (D + 1) acts on 1 (not written explicitly, but it's really there) which results in - (D + 1)1 = - D1 - 1 after distribution. Now since 1 is a constant, and D is the derivative, - D1 = 0; that's how you get rid of - D. Otherwise you have everything else correct.

I hope this helps.... Did you know you can get 3 points back by picking a best answer?
Thank you sooo mcuh. This just made my life easier!

There are currently no comments for this question.

This question about "How do you get this … " was originally asked on Yahoo Answers United States

• by Helen
Member since:
October 27, 2008
Total points:
676 (Level 2)
i get the same as u :s

3(D+1)x + (D+1)(D+2)y - [3(D+1)x + 3(D-1)y] = -(D+1) -6

3(D+1)x + (D+1)(D+2)y -3(D+1)x - 3(D-1)y = -D - 7

(D+1)(D+2)y - 3(D-1)y = -D-7

(D^2 + 3D + 2) y (-3D +3)Y = -D-7

(D^2 +5)y = -D-7